Participatory rangeland management (PRM) being piloted in Kenya and Tanzania covering 246,773 ha of pastoralists' communal grazing lands, and upscaled in Ethiopia (Updated 2020) - CGIAR Research Program on Livestock (2020)
Participatory rangeland management (PRM) was developed by ILRI and partners in Ethiopia, piloted and then upscaled. PRM improves the productivity of rangelands and access to resources for local rangelands users (communities). In 2018, the European Union invested Euro 1.5 million in the Piloting of PRM Project in Baringo County, Kenya and six shared grazing lands in Tanzania (targeting 450,000 pastoralists and agropastoralists). In 2020/21 PRM is being upscaled through a USD 30 million investment on 8.8 million hectares in Ethiopia.